2006
DOI: 10.1111/j.0014-3820.2006.tb01859.x
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Natural and Sexual Selection During Adaptation to a Novel Environment

Abstract: Abstract. The net effect of sexual selection on nonsexual fitness is controversial. On one side, elaborate display traits and preferences for them can be costly, reducing the nonsexual fitness of individuals possessing them, as well as their offspring. In contrast, sexual selection may reinforce nonsexual fitness if an individual's attractiveness and quality are genetically correlated. According to recent models, such good-genes mate choice should increase both the extent and rate of adaptation. We evolved 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
121
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(130 citation statements)
references
References 69 publications
8
121
1
Order By: Relevance
“…No such promotion was detected. The same was true for Drosophila serrata selected for adaptation to novel food (Rundle et al 2006). However, Dolgin et al (2006) have recently found that adaptation to thermal environment did increase male mating success.…”
Section: Variable Environmentmentioning
confidence: 82%
See 1 more Smart Citation
“…No such promotion was detected. The same was true for Drosophila serrata selected for adaptation to novel food (Rundle et al 2006). However, Dolgin et al (2006) have recently found that adaptation to thermal environment did increase male mating success.…”
Section: Variable Environmentmentioning
confidence: 82%
“…One-way to test whether sexual selection increases population fitness is experimental evolution under varying opportunities for sexual selection (e.g. Holland 2002; Radwan et al 2004;Rundle et al 2006;Fricke and Arnqvist 2007). …”
Section: Experimental Evolutionmentioning
confidence: 99%
“…Several experiments have manipulated the opportunity for sexual selection and then measured the consequences for population mean fitness or components thereof, beginning either from standing genetic variance [4,[15][16][17][18][19][20][21][22][23][24] or from novel mutational variance [25][26][27]. This approach integrates genetic effects across much of the genome, meaning the net effect on fitness may be dominated by sets of segregating alleles with opposing effects on sexual versus nonsexual fitness, obscuring underlying patterns at individual loci.…”
Section: Resultsmentioning
confidence: 99%
“…To provide insight into the impact of sexual selection on naturally segregating polymorphisms across the genome, we previously evolved 12 populations of Drosophila serrata in a novel environment employing a factorial manipulation of the opportunities for natural and sexual selection [4]. Here, we genotype more than 1,400 SNPs in the evolved populations and reveal that sexual selection affected many of the same genomic regions as natural selection, aligning with it as often as opposing it.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual conflict has been extensively studied in D. melanogaster [49,58,59] and D. serrata males are likewise also known to be harmful to females [43]. Reduced attractiveness of females when mating activity is highest may therefore be an adaptive response in females to ongoing interlocus conflict, allowing them to reduce costly male harassment and/or to avoid possibly harmful matings.…”
Section: Discussionmentioning
confidence: 99%